2009
DOI: 10.1177/1010539509343958
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes Mellitus, Glycemic Control, and Associated Factors in a Malay Population in Singapore

Abstract: There is substantial heterogeneity regarding diabetes mellitus prevalence and glycemic control in Asian populations. The authors examined a population-based sample of 3000 adults (52% women) of Malay ethnicity (40-80 years) in Singapore. The age-standardized prevalence of diabetes mellitus was 18.4% (95% confidence interval = 17.0% to 19.8%). Being overweight, presence of hypertension, presence of cardiovascular disease, and family history of diabetes were found to be positively associated with diabetes mellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
(35 reference statements)
4
17
1
Order By: Relevance
“…In a 3‐year prospective study of DM control among different ethnic groups in Singapore, Malay patients had significantly higher HbA1c compared with Chinese and Indian at baseline, and consistently for all years of HbA1c assessment . In another epidemiology study of 3000 adults of Malay ethnicity between 40 and 80 years old in Singapore, 71% had suboptimal glycemic control . It is plausible that the association of MRSA colonization and Malay ethnicity is a result of poor glycemic control instead of ethnic predisposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 3‐year prospective study of DM control among different ethnic groups in Singapore, Malay patients had significantly higher HbA1c compared with Chinese and Indian at baseline, and consistently for all years of HbA1c assessment . In another epidemiology study of 3000 adults of Malay ethnicity between 40 and 80 years old in Singapore, 71% had suboptimal glycemic control . It is plausible that the association of MRSA colonization and Malay ethnicity is a result of poor glycemic control instead of ethnic predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…16 In another epidemiology study of 3000 adults of Malay ethnicity between 40 and 80 years old in Singapore, 71% had suboptimal glycemic control. 20 It is plausible that the association of MRSA colonization and Malay ethnicity is a result of poor glycemic control instead of ethnic predisposition. Environmental factors such as living conditions 21 and socioeconomic factors might be associated with MRSA transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a follow-up duration of less than twelve months were excluded in order to avoid the immediate period following diagnosis and to obtain adequate time for observing adherence (Donnan et al 2002). Sample size was determined using two proportion formula considering a 95% confidence level, power of 80%, and various factors that were known to influence diabetes medication adherence, and resulted in a sample size of 407 (Sabanayagam et al 2009; Khattab et al 2010). The follow-up record book was used as a sampling frame to randomly select eligible study subjects.…”
Section: Methodsmentioning
confidence: 99%
“…The age-standardized prevalence of DM in 3000 adults (52% women) of Malay ethnicity (40-80 years) in Singapore was 18.4%. 14 The age-adjusted prevalence of IFG and DM diabetes in the Korean population were 23.9% and 7.6%, respectively. 15 A study on US immigrants showed that age-and gender adjusted DM prevalence ranged from 3.1% among European migrants to 10.0% among migrants from the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 99%